Factors influencing diarrheal prevalence among children under five years in Mathare Informal Settlement, Nairobi, Kenya - Djounfoune A. Guillaume; Osero O.S. Justus; Kabiru W. Ephantus (AOSIS, 2020)
Globally, diarrhoea is the second major cause of death among children under five years. The aim of the study was to establish factors influencing diarrhoeal prevalence among children under five years in Mathare Informal Settlement. Cross-sectional survey was used. Data was collected from 1st July to 1st August 2019 among primary care- givers (PCGs) of children under five years in Mathare Informal Settlement, in Nairobi, Kenya. This urban informal settlement in Kenya was purposively sampled. Simple random sampling was used to select the households and the respondents. P0.05 was considered as statistically significant. A total of 324 primary caregivers selected from 324 households were included in the study. Fifty six point seventeen percent of the respondents were aged 25-31 years old. Prevalence of diarrhoea among children was 18.7%. Sex, relationship of the primary caregivers, number of people and children in the households were found to be statisti- cally significant with diarrhoea prevalence with p=0.008, p0.001, p0.001, p0.001 respectively. One hundred and seventy one (52.78%) primary caregivers had no formal education. primary caregivers disposed of the child's faeces in garbage in 38.89% of the cases. Education level of the primary caregivers, renting, presence of flies, fae- ces, and open garbage near or within the compound were found to be associated with diarrhoea prevalence with p0.001, p=0.024, p0.001, p0.001 respectively. Several factors were found to be associated with diarrhoeal prevalence among children under five years.